Respon Petani Terhadap Teknologi Pengolahan Lahan Budidaya Cabai di Desa Golo Pua, Kecamatan Kuwus, Kabupaten Manggarai Barat - Marsianus Suryadi; Sad Likah; Laurensius Halu (Jurnal Penyuluhan Pembangunan, 2024)
ABSTRACTThis study aims to determine the response of farmers to chili cultivation land processing technology in Golo Pua Village, Kuwus District, West Manggarai Regency. This type of research is a survey. Data collection techniques through questionnaires and observation. The survey results showed that the pretest results for 30 respondents obtained the lowest score was 3 and the highest score was 12, those who had high category knowledge were 6 respondents, moderate category knowledge were 22 respondents, low category knowledge was 1 respondent and very low category knowledge was 1 respondent. The percentage of pre-test knowledge is 52.35%. The results of the post test showed that the lowest score was 11 and the highest score was 17, 21 respondents had very high category knowledge, 9 respondents had high category knowledge. The percentage of post test knowledge is 85.29%. This means that counseling about chili cultivation land processing technology is able to increase respondents' knowledge. Based on the results of observations using the skills observation sheet, it was obtained by respondents with high skills as many as 30 people with a percentage of the skill aspect of chili farmers of 93.61%.